Breathe : a ghost story - McNish, Cliff (Minneapolis, MN : Carolrhoda Books, 2006)
When he and his mother move into an old farmhouse in the English countryside, asthmatic, twelve-year-old Jack discovers that he can communicate with the ghosts inhabiting the house and inadvertently establishes a relationship with a tormented, malevolent spirit that threatens to destroy both his mother and himself.
Wilson's Junior High School, August 2007.
School Library Journal, November 2006.
Horn Book, April 2007.
Voice of Youth Advocates (V.O.Y.A.), December 2006.
Wilson's Junior High School.
School Library Journal.
Keywords: Extrasensory perception -- Juvenile fiction; Asthma -- Juvenile fiction; Single-parent families -- Juvenile fiction; Death -- Juvenile fiction; Grief -- Juvenile fiction; Extrasensory perception -- Fiction; Asthma -- Fiction; Single-parent families -- Fiction; Death -- Fiction; Grief -- Fiction; Ghosts -- Fiction; Extrasensory perception -- Fiction; Asthma -- Fiction; Single-parent families -- Fiction; Death -- Fiction; Grief -- Fiction; Ghost stories; Ghosts -- Fiction; Extrasensory perception -- Fiction; Asthma -- Fiction; Single-parent families -- Fiction; Death -- Fiction; Grief -- Fiction; England -- Juvenile fiction; England -- Fiction; England -- Fiction; England -- Fiction; Ghost stories